2013
DOI: 10.1159/000353456
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings Associated with Cognitive Performance in Primary Lateral Sclerosis and Amyotrophic Lateral Sclerosis

Abstract: Introduction: Executive dysfunction occurs in many patients with amyotrophic lateral sclerosis (ALS), but it has not been well studied in primary lateral sclerosis (PLS). The aims of this study were to (1) compare cognitive function in PLS to that in ALS patients, (2) explore the relationship between performance on specific cognitive tests and diffusion tensor imaging (DTI) metrics of white matter tracts and gray matter volumes, and (3) compare DTI metrics in patients with and without cognitive and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…Clinical measures of cognitive status were not associated with PBA. Although previous studies found alterations in extramotor cortical areas associated with cognitive dysfunction in ALS or PLS, 11,38 the primary structural correlates seem to be interhemispheric long association tracts. However, an association between oral naming and integrity of portions of cerebellar white matter was reported in one recent study 39 that defined cognitive impairment in PLS less stringently than consensus criteria and did not assess for concurrent PBA.…”
Section: Statistical Analysis Of Clinical Data Continuous Demographicmentioning
confidence: 66%
“…Clinical measures of cognitive status were not associated with PBA. Although previous studies found alterations in extramotor cortical areas associated with cognitive dysfunction in ALS or PLS, 11,38 the primary structural correlates seem to be interhemispheric long association tracts. However, an association between oral naming and integrity of portions of cerebellar white matter was reported in one recent study 39 that defined cognitive impairment in PLS less stringently than consensus criteria and did not assess for concurrent PBA.…”
Section: Statistical Analysis Of Clinical Data Continuous Demographicmentioning
confidence: 66%
“…18,28 Most DTI studies have not found significant group level differences outside motor tracts in DTI, however, in patients who have mild cognitive impairment, small and scattered diffusion changes may be seen in extramotor association tracts. 30,31 MRI sequences specific for myelin also show a broader distribution of white matter changes than are seen with DTI. 32 …”
Section: Diagnosismentioning
confidence: 95%
“…80 Investigations of cognitive deficits in ALS, FTD and ALS-FTD patients have been found to covary with reduction of GM in several regions of the temporal lobes, including the hippocampal formation and amygdala as well as a loss of integrity of the WM networks connecting frontotemporal areas to parietal and occipital areas, including uncinate and longitudinal fasciculus. 9,54,[81][82][83][84][85][86][87][88][89][90][91][92][93] Episodic memory Amnesia, in particular, is problematic as a symptom in ALS and FTD, as it is currently considered as the diagnosis gold standard for underlying Alzheimer's disease pathophysiology. By contrast, episodic memory is considered to be preserved in the ALS-FTD spectrum and therefore, severe amnesia is even stated as a diagnostic exclusion criterion for the behavioural variant of FTD.…”
Section: Clinical/neuropsychological Findingsmentioning
confidence: 99%